Analisis permasalahan proses pembelajaran bahasa jawa materi geguritan kelas IV sekolah dasar - Widiandhieka, Ananda Pangesthi Tri; Winarni, Retno; Daryanto, Joko (Universitas Sebelas Maret, 2023)
This study aims to analyze the problems of the Javanese learning process of grade IV poetry material at SDN Mangkubumen Lor No. 15 Surakarta and the causes of problems in the Javanese learning process of grade IV poetry material at SDN Mangkubumen Lor No. 15 Surakarta. This research is a type of qualitative research with a content analysis design. The data collection techniques used in this study include interviews and questionnaires with data analysis using interactive analysis models. The results of the research obtained show that the problem in the learning process of Javanese poetry material at SDN Mangkubumen Lor No. 15 Surakarta is that students have difficulty in understanding the vocabulary and meaning of each word in poetry, as well as the culture of using Javanese that is not used to it in everyday life also affects their difficulty in understanding Javanese learning poetry material. Moreover, the cause of students' problems in the Javanese learning process in poetry material at SDN Mangkubumen Lor No. 15 Surakarta is due to internal factors including lack of concentration, lack of self-confidence and lack of motivation.